HKUST-1 (at) CNF composite material as well as preparation method and application thereof
By using HKUST-1@CNF composite material, the problem of insufficient mechanical strength and cycle stability of the aqueous zinc ion battery separator material is solved, efficient zinc dendrites inhibition and electrochemical performance improvement are achieved, and a more stable battery separator is provided.
Patent Information
- Application Number
- CN202411690267.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-14
AI Technical Summary
The existing aqueous zinc ion battery separator materials have shortcomings in terms of mechanical strength and cyclic stability, resulting in uneven growth of zinc dendrites and short-circuit failures, affecting the electrochemical performance of the battery.
Using HKUST-1@CNF composite material as the separator material, the mixing of HKUST-1 with cellulose suspension and polar solvent in a specific proportion, and agitation grafting reaction and film extraction process is carried out to form an excellent pore structure and high machinery. Battery separator with strength.
Effectively inhibit the uneven growth of zinc dendrites, improve the cycle stability and Coulomb efficiency of the battery, significantly improve the comprehensive electrochemical performance of the diaphragm, and maintain high ionic conductivity and mechanical strength.
Smart Images

Figure CN119306956A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a HKUST-1 composite material and a preparation method and application thereof, and more specifically, to a HKUST-1@CNF composite material and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) are an emerging energy storage system with high safety, high ionic conductivity and high theoretical capacity. In addition, high-capacity zinc metal anodes (820 mA h g -1 / 5855 mA h cm -3 ) can compensate for the energy density loss caused by the voltage limitation of aqueous electrolytes. Therefore, ZIBs have broad application prospects in large-scale energy storage systems and smart wearable devices.
[0003] The separator is the main component of the battery, which can prevent the positive and negative electrodes from directly contacting each other, thus causing a short circuit and forming a "dead battery". In addition, the separator can absorb electrolyte to provide an efficient channel for ion migration. At present, glass fiber (GF), hydrophilic polyolefin (HPP), etc. are often used as ZIBs separators. GF has rich pores and good hydrophilicity. After being filled with electrolyte, it can reach an electrolyte absorption rate of 300% and has high ionic conductivity (≈17.3 mS cm -1 ), which is compatible with various electrodes, but the GF separator cannot resist zinc dendrite puncture due to its low mechanical strength. In addition, its considerable thickness (600 µm) takes up too much space in the battery, and its high price makes it difficult to control the energy density cost per unit cell. The HPP separator has high porosity and excellent insulation, however, it is prone to short-circuit failure due to its low thermal / mechanical stress tolerance and inability to prevent thermal runaway when the battery is cycled for a long time. In addition, its pore distribution is usually inconsistent and the electric field uniformity is poorly controlled, resulting in uneven zinc deposition, which affects the electrochemical performance of the battery.
[0004] Cellulose, as a material with abundant reserves, low cost and high mechanical strength, can be used to manufacture electrodes with high power density and high energy density, lightweight current collectors and functional diaphragms. HKUST-1 has excellent thermal stability, adjustable pore structure, diversified functions, high specific surface area and porosity, and is a potential diaphragm material; in addition, HKSUT-1 can significantly improve the screening ability of ions, and its three-dimensional inherent pores can provide additional high-speed channels for ion transport, which can effectively prevent the shuttle effect of electrode materials. Therefore, selecting HKSUT-1 as a modified material for cellulose battery diaphragms can improve its shortcomings while retaining the excellent properties of cellulose diaphragms, thereby improving the comprehensive performance of the diaphragms. At present, there has been no research on the selection of HKUST-1 as a modified material for cellulose battery diaphragms. Summary of the invention
[0005] The present invention mainly aims at the problem of weak electrochemical performance of existing battery separator materials, and provides a HKUST-1@CNF composite material. The HKUST-1@CNF composite material is prepared by cleverly utilizing the excellent hydrothermal stability, adjustable pore structure, and diversified functions of HKUST-1, as well as the excellent mechanical strength of cellulose, for the performance study of aqueous zinc ion battery separators. The HKUST-1@CNF battery separator can effectively inhibit the uneven growth of zinc dendrites and the occurrence of side reactions, maintain a high coulombic efficiency in long cycles, and has excellent cycle stability. The overall electrochemical performance of the HKUST-1@CNF battery separator has been greatly improved, and it can be widely used.
[0006] Another object of the present invention is to provide a method for preparing the HKUST-1@CNF composite material.
[0007] Another object of the present invention is to provide an application of the HKUST-1@CNF composite material.
[0008] The present invention is achieved through the following technical solutions: A HKUST-1@CNF composite material, wherein the HKUST-1@CNF composite material is prepared by reacting the following components in parts by weight: HKUST-1: 0~10 copies Cellulose (CNF) suspension: 1-100 parts The weight ratio of the HKUST-1 to the CNF suspension is 0-1:0.1-10.
[0009] Furthermore, the components of the HKUST-1@CNF composite material also include a polar solvent, and the weight of the polar solvent is no more than 40 times the weight of the HKUST-1 component.
[0010] Further optimized, the HKUST-1@CNF composite material is prepared by reacting the following components in parts by weight: HKUST-1: 0~10 copies Cellulose (CNF) suspension: 1-100 parts Polar solvent: 10-400 parts The present invention utilizes HKUST-1's adjustable pore structure, diversified functions and excellent hydrothermal stability, and is a potential diaphragm material; in addition, HKSUT-1 can significantly improve the ion screening ability, and its three-dimensional penetrating inherent pores can provide additional channels for ion transmission, which can effectively prevent the shuttling effect of electrode materials and effectively inhibit the generation of irregular and uneven zinc dendrites.
[0011] Moreover, cellulose, as a material with abundant reserves, low cost and high mechanical strength, can be used to manufacture electrodes with high power density and high energy density, lightweight current collectors and functional separators. This method uses the stable metal organic framework HKUST-1 material for the first time to prepare HKUST-1@CNF composite materials, and the battery separator made of this material can maintain a high coulombic efficiency in long cycles and has excellent cycle stability and electrochemical performance.
[0012] Another object of the present invention is to disclose a method for preparing the HKUST-1@CNF composite material, the method comprising the following steps: S1. Add the CNF suspension and polar solvent in the above ratio to beaker A, stir and disperse for 8-12h to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 8-12h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 80-100°C for 4-6 hours to obtain the HKUST-1@CNF composite material.
[0013] Furthermore, the HKUST-1@CNF composite material is characterized in that the HKUST-1 is a type of metal-organic framework material having a copper acetate paddle wheel structure and one or more of different morphologies, and the HKUST-1 is a metal-organic framework material synthesized by copper ions and 1,3,5-benzenetricarboxylic acid.
[0014] Furthermore, the HKUST-1@CNF composite material is characterized in that the HKUST-1 can be HKUST-1 with various morphologies such as micron-scale, nano-scale, and graded pores.
[0015] Furthermore, the HKUST-1 with micron-scale, nano-scale and hierarchical pore morphologies is characterized in that the HKUST-1 with different morphologies is obtained by cross-sampling with different copper sources and copper source solvents.
[0016] Furthermore, the HKUST-1@CNF composite material is characterized in that the polar solvent is one or more of ethanol, methanol, and n-butanol.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The HKUST-1@CNF composite material provided by the present invention uses common raw materials, creatively uses HKUST-1 and CNF in the preparation of battery separator materials, and has a special structure of metal organic framework materials on the fiber strips. The prepared HKUST-1@CNF composite material maintains a high coulomb efficiency in a long cycle, has high mechanical strength and good cycle stability.
[0018] The preparation of the HKUST-1@CNF composite material of the present invention is based on the blending grafting and film extraction process, the preparation process is simple, the cost is low, the prepared HKUST-1@CNF composite material has good comprehensive performance, a wide range of applications, and is safe and reliable during use.
[0019] The HKUST-1@CNF composite material of the present invention can achieve a maximum ionic conductivity of 5.74 mS cm while ensuring the mechanical strength of the battery separator material. -1 The ionic conductivity of HKUST-1@CNF membrane was 90% higher than that of pure CNF membrane. HKUST-1@CNF membrane maintained high coulombic efficiency in long cycles and failed only at the 633rd cycle. However, CNF membrane failed at the 189th cycle. -2 , 1 mAh cm -2 The zinc symmetric battery remained stable in a cycle test of up to 1500 h without short circuit. The HKUST-1@CNF composite material prepared by the present invention has good comprehensive electrochemical performance, strong product stability, and can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The SEM images of the HKUST-1@CNF battery separator of Example 2 at different magnifications; Figure 2 This is a comparison chart of the half-cell coulombic efficiency of the HKUST-1@CNF battery separator of Example 2; Figure 3 The HKUST-1@CNF battery separator of Example 2 is 1 mA·cm -2 、1 mAh·cm -2 Cycling performance of zinc symmetric batteries under . DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with the attached table and specific examples. Unless otherwise specified, the various raw materials used in the embodiments of the present invention can be purchased from the conventional market, or prepared according to the conventional methods in the art, and the equipment used is the common experimental equipment. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art.
[0022] The present invention creatively selects HKUST-1, CNF suspension and polar solvent for synthesis, and the HKUST-1@CNF composite material with uniform dispersion and good electrochemical performance is prepared by reaction.
[0023] HKUST-1 is a metal-organic framework material synthesized from copper ions and 1,3,5-benzenetricarboxylic acid.
[0024] CNF suspension was purchased through Taobao The polar solvent is one or more of ethanol, methanol and n-butanol. Example 1
[0025] Select the material ratio in Table 1.
[0026] S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 12 hours to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 12h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 80°C for 6 h to obtain the HKUST-1@CNF composite material.
[0027] The performance test results of the prepared HKUST-1@CNF composite material are shown in Table 2. Example 2
[0028] Select the material ratio in Table 1.
[0029] S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 10 hours to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 10h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 80°C for 4 h to obtain the HKUST-1@CNF composite material. The surface morphology of the membrane is shown in Figure 2. Figure 1 As shown in the figure, the overall structure of the separator is displayed at low magnification, with granular HKUST-1 attached to the fiber strips; at high magnification, it can be observed that the HKUST-1 particles are grafted with the fibers in an interlaced manner, and there is a phenomenon of interlaced fusion with the fibers. This distribution helps to improve the overall mechanical strength and functionality of the membrane, and can also improve its electrolyte absorption capacity and ion conductivity, thereby showing better performance in battery performance.
[0030] The performance test results of the prepared HKUST-1@CNF composite material are shown in Table 2, and the coulombic efficiency performance of the half-cell is shown in Figure 2 As shown in Figure 2, the HKUST-1@CNF battery separator still maintains a high coulombic efficiency at the 632nd cycle, which improves the stability of the battery. Figure 3 As shown in the figure, HKUST-1@CNF has good cycle stability, can maintain stable cycle for 1550 h, and has a lower polarization voltage. This is because the developed pore structure of HKUST-1 not only improves the ion transmission efficiency, but also provides a buffer space to absorb current fluctuations, reduce voltage fluctuations and polarization, and improve the cycle stability and safety of the battery. Example 3
[0031] Select the material ratio in Table 1.
[0032] S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 12 hours to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 12h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 100°C for 6 h to obtain the HKUST-1@CNF composite material.
[0033] The performance test results of the prepared HKUST-1@CNF composite material are shown in Table 2. Example 4
[0034] Select the material ratio in Table 1.
[0035] S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 10 hours to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 10h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 100°C for 4 h to obtain the HKUST-1@CNF composite material.
[0036] The performance test results of the prepared HKUST-1@CNF composite material are shown in Table 2. Example 5
[0037] Select the material combination in Table 1.
[0038] S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 12 hours to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio and stir the grafting reaction for 12h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 80°C for 5 h to obtain the HKUST-1@CNF composite material.
[0039] The performance test results of the prepared HKUST-1@CNF composite material are shown in Table 2.
[0040] Table 1 HKUST-1 (g) CNF suspension (g) Polar solvent (mL) Example 1 0.0075 4 50 Example 2 0.0225 4 50 Example 3 0.0375 4 50 Example 4 0.0525 4 50 Example 5 0.0675 4 50 Table 2 <![CDATA[Ionic conductivity (mS cm -1 ).]]> Coulomb efficiency (%) Zinc symmetric cycle performance (h) Example 1 2.66 97.9 (541 laps) 600 Example 2 5.74 99.8 (632 laps) 1550 Example 3 5.65 99 (605 laps) 600 Example 4 4.05 99 (275 laps) 450 Example 5 2.75 99 (189 laps) 296
Claims
1. A HKUST-1@CNF composite material, characterized in that: The HKUST-1@CNF composite material is prepared by reacting the following components in parts by weight: HKUST-1: 0~10 copies Cellulose (CNF) suspension: 1-100 parts The weight ratio of the HKUST-1 to the CNF suspension is 0-1:0.1-10.
2. The HKUST-1@CNF composite material according to claim 1, characterized in that: The components of the HKUST-1@CNF composite material also include a polar solvent (ethanol), and the weight of the polar solvent is no more than 40 times the weight of the HKUST-1 component.
3. The HKUST-1@CNF composite material according to claim 2, characterized in that: The HKUST-1@CNF composite material is prepared by reacting the following components in parts by weight: HKUST-1: 0~10 copies Cellulose (CNF) suspension: 1-100 parts Polar solvent: 10-400 parts.
4. The HKUST-1@CNF composite material according to claim 1, characterized in that: The HKUST-1 is a type of metal organic framework material having a copper acetate paddle wheel structure and one or more of different morphologies. The HKUST-1 is a metal organic framework material synthesized by copper ions and 1,3,5-benzenetricarboxylic acid.
5. The HKUST-1@CNF composite material according to claim 1, characterized in that: The HKUST-1 is HKUST-1 with various morphologies such as micron-scale, nano-scale, and graded pores.
6. The HKUST-1@CNF composite material according to claim 2, characterized in that: The polar solvent is one or more of ethanol, methanol and n-butanol.
7. A method for preparing the HKUST-1@CNF composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1. Add the CNF suspension and polar solvent to beaker A in the above ratio, stir and disperse for 8-12h to form a uniform CNF dispersion, centrifuge and wash to remove excess water, and then put it into beaker A; S2. Add HKUST-1 to beaker A in the above ratio, stir, and blend and graft for 8-12h; S3. The mixed solution of HKUST-1 and CNF in beaker A was drawn into a film, and the film was placed in an oven and vacuum dried at 80-100°C for 4-6 hours to obtain the HKUST-1@CNF composite material.
8. The HKUST-1@CNF composite material prepared by the preparation method according to claim 7 is applied to a battery separator in an aqueous zinc ion battery.
Citation Information
Patent Citations
Cellulose nanofibril / metal-organic framework composite lithium ion battery separator and preparation method
CN108428841A
MOF (Metal Organic Framework) modified bacterial cellulose composite membrane as well as preparation and application thereof
CN118630424A
Preparation method and application of 1D HKUST-1 / PEO-based solid electrolyte membrane
CN118738538A
Cited By
Aluminum fumarate-cellulose composite material, preparation method thereof and application of aluminum fumarate-cellulose composite material in aqueous zinc ion battery diaphragm
CN121054960A